Incursion of tropically-distributed plant taxa into high latitudes during the middle Eocene warming event: Evidence from the Río Turbio Fm, Santa Cruz, Argentina - Fernández, Damián Andrés; Santamarina, Patricio Emmanuel; Palazzesi, Luis; Tellería, María Cristina; Barreda, Viviana Dora (Review of Palaeobotany and Palynology)
Plant species with predominantly tropical and subtropical modern distributions (or meso-megathermal species) penetrated into the highest southern latitudes of the American continent during the global warmest periods of the Cenozoic. These species – usually phylogenetically unrelated – became fossilized typically as dispersed spores and pollen grains. Here, we describe and illustrate fossil spores and pollen grains preserved during the Middle Eocene Climatic Optimum (MECO) in Patagonian southernmost latitudes (Río Turbio Formation). We study those species that today occurred in lower latitudes (e.g. northern Argentina and Brazil) and became locally extinct from Patagonia during the subsequent cooling episodes. We also estimate their frequency in the paleofloras. Our records show the presence of: Arecaceae, Cardiospermum (Sapindaceae), Cathedra (Olacaceae), Ceiba (Malvaceae, Bombacoideae), Cupania (Sapindaceae), Ilex (Aquifoliaceae), Malpighiaceae, Spathiphyllum (Araceae), Trimeniaceae, and tropical ferns, as Cnemidaria (Cyatheaceae) and Lygodium (Lygodiaceae). The angiosperm families are mostly pollinated by animals, especially insects. We found that these lineages occurred more frequently during MECO samples (~40 Mya) than in older (~44 Mya) and younger (~37 Mya) samples, suggesting that the southern dispersion of tropical elements occurred in waves, following this greenhouse episode. The study of fossil forms assigned to tropical families has previously been neglected in favor of Gondwanan canopy members such as southern beeches and podocarps. Our contribution sheds light into the most underrepresented members of the paleoflora and their key role in past plant–pollinator interactions. Fil: Fernández, Damián Andrés. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Universidad Nacional de Tierra del Fuego, Antártida e Islas del Atlántico Sur. Instituto de Ciencias Polares, Ambientales y Recursos Naturales; Argentina Fil: Santamarina, ...